War and Genocide in South Sudan - Pinaud, Clémence (Cornell University Press, 2022)
Using more than a decade's worth of fieldwork in South Sudan, Clémence Pinaud here explores the relationship between predatory wealth accumulation, state formation, and a form of racism-extreme ethnic group entitlement-that has the potential to result in genocide. War and Genocide in South Sudan traces the rise of a predatory state during civil war in southern Sudan and its transformation into a violent Dinka ethnocracy after the region's formal independence. That new state, Pinaud argues, waged genocide against non-Dinka civilians in 2013-2017. During a civil war that wrecked the region between 1983 and 2005, the predominantly Dinka Sudan People's Liberation Army (SPLA) practiced ethnically exclusive and predatory wealth accumulation. Its actions fostered extreme group entitlement and profoundly shaped the rebel state. Ethnic group entitlement eventually grew into an ideology of ethnic supremacy. After that war ended, the semi-autonomous state turned into a violent and predatory ethnocracy-a process accelerated by independence in 2011. The rise of exclusionary nationalism, a new security landscape, and inter-ethnic political competition contributed to the start of a new round of civil war in 2013, in which the recently founded state unleashed violence against nearly all non-Dinka ethnic groups. Pinaud investigates three campaigns waged by the South Sudan government in 2013-2017 and concludes they were genocidal-they sought to destroy non-Dinka target groups. She demonstrates how the perpetrators' sense of group entitlement culminated in land-grabs that amounted to a genocidal conquest echoing the imperialist origins of modern genocides. Thanks to generous funding from TOME, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.